A novel family of non-symmetric benzothieno[7, 6-b]-fused BODIPYs: Synthesis, structures, photophysical properties and lipid droplet-specific imaging in vitro. (December 2021) - Zhao, Yuanyuan; Zhao, Yu; Yu, Changjiang; Liu, Suowei; Liu, Yang; Hao, Erhong; Jiao, Lijuan; Xu, Xinming; Zhang, Zhen; Li, Jiazhu
Abstract: The synthesis of near-infrared emitting BODIPY fluorophore is a key requirement for biomedical imaging applications. Herein, a series of non-symmetric benzothieno[7, 6- b ]-fused BODIPY dyes were efficiently synthesized. All of them have been well characterized by NMR ( 1 H, 13 C, 11 B, 19 F), HRMS, UV–vis, Emission, and X-ray crystal analysis. These dyes exhibit effective planar expansion of π-conjugation on the BODIPY core. The absorption from 540 to 700 nm and emission from 620 to 780 nm are effectively tuned by benzothieno[7, 6- b ] fusion or Knoevenagel condensation reaction. More importantly, these developed dyes showed high specificity for staining lipid droplets. Cell imaging experiments demonstrated that a benzothieno[7, 6- b ]-fused BODIPY with para -dimethylaminophenyl group exhibited high photo-stability for imaging in living cell. The synthesis and functional modification for the benzothieno[7, 6- b ]-fused BODIPY dye provided an effective way for generating BODIPY-based near-infrared dyes in medical and biological applications. Graphical abstract: Novel non-symmetric benzothieno[7, 6- b ]-fused BODIPYs with NIR emission were synthesized, which showed high specificity for staining lipid droplets and high photo-stability in living cell. Image 1